Kant’s Machiavellian Moment - Foster, Jay (Con-Textos Kantianos. International Journal of Philosophy, 2015)
At least two recent collections of essays – Postmodernism and the Enlightenment (2001) and What’s Left of Enlightenment?: A Postmodern Question (2001) – have responded to postmodern critiques of Enlightenment by arguing that Enlightenment philosophes themselves embraced a number of post-modern themes. This essay situates Kant’s essay Was ist Aufklärung (1784) in the context of this recent literature about the appropriate characterization of modernity and the Enlightenment. Adopting an internalist reading of Kant’s Aufklärung essay, this paper observes that Kant is surprisingly ambivalent about who might be Enlightened and unspecific about when Enlightenment might be achieved. The paper argues that this is because Kant is concerned less with elucidating his concept of Enlightenment and more with characterizing a political condition that might provide the conditions for the possibility of Enlightenment. This paper calls this political condition modernity and it is achieved when civil order can be maintained alongside fractious and possibly insoluble public disagreement about matters of conscience, including the nature and possibility of Enlightenment. Thus, the audience for the Aufklärung essay is not the tax collector, soldier or clergyman, but rather the sovereign. Kant enjoins and advises the prince that discord and debate about matters of conscience need not entail any political unrest or upheaval. It is in this restricted (Pocockian) sense that the Enlightenment essay is Kant’s Machiavellian moment.